(untitled) (Tanzania Medical Journal, 2007)
Background: Previous studies in the public sector in Tanzania, have demonstrated major prescribing problems due to poly-pharmacy and irrational use of antibiotics and injections. Little is understood about prescribing in the private sector. Broad objective: This paper measures and compares prescribing practices in public and private dispensaries in Kibaha District Tanzania. Design and Sampling: This was a retrospective survey of patient records for the period January – December, 2002.One thousand patient records were randomly selected from public dispensaries and 1,000 from private dispensaries. WHO drug use indicators were used to assess prescribing in both sectors. Outcome measures: The following WHO indicators were measured; the average number of drugs per patient, percentage antibiotic prescriptions, percentage injection prescriptions, percentage of drugs prescribed in generic names and percentage of prescriptions according to national essential drug list of Tanzania (NEDLIT). Results: Prescribing of antibiotic and injections was significantly higher in private than in public dispensaries (P